Nov, na prstnem odtisu temelječ biometrični varnostni sistem - Lalović, Komlen; Trajkovic, Dalibor; Bacanin Dzakula, Nebojsa (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
The article presents a completely new system of biometric identification and ensuring the identity of an infant, based on the minutiae of fingerprints. These are the only biometric data that are formed prenatally in humans. We present a qualitative study that proves that an infant has a fingerprint that can be obtained, stored, encrypted and, above all, ensure its identity. We tested the child's minutiae on all possible types of fingerprint readers and found out which one is optimal for this purpose. This has laid a solid foundation for further development of our research. All this confirms that this is a major social problem worldwide, which requires a solution with 100% accuracy in hospitals and maternity hospitals in every country, since cases of child switching have occurred on almost all continents of the world. The first step was to create a prototype of our patented device. It is a dual fingerprint scanner that scans two fingers, the mother's and the child's, simultaneously or with an interval of a few seconds.